Overview of the formation and development of Chinese language literature in Thailand: DOI: https://doi.org/10.17721/1728-242X.2022.28.30-33 (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
The Thai-Chinese literature represents more than century-old experience of Chinese immigrants in Thailand recorded in literary works. It is the embodiment of life's vocations, dreams and thoughts of Chinese immigrants, as well as an important symbol of the struggle for Chinese cultural identity. In modern Thailand, the native language of ethnic Chinese is Thai. For the Thai population, Chinese is the second foreign language to learn while English is the first. In the realities of the lack of permanent cultural ties and a stable language environment, Chinese-language writings in Thailand are unique and special in their subject matter and issues. Given the fact that studies of Overseas Chinese literature of the twentieth and twenty-first centuries in the world are mostly focused on literary works in North America, the study of Chinese-language literature in Southeast Asia, in particular Thai-Chinese literature, receives less attention. The oeuvre and achievements of this literature have not yet received a proper deep and detailed scientific understanding and assessment of the aesthetic features and uniqueness of this literary phenomenon. And this is the reason why the study of modern Thai-Chinese literature is of great importance. This paper is of an overview character and is devoted to the formation and development of Thai Chinese-language literature from the early twentieth century to the present. Particular attention has been paid to the challenges and obstacles that have accompanied the development of Chinese-language writing in Thailand throughout history. Readers are also invited to get acquainted with the Ukrainian translation of the short story by the Thai writer of Chinese origin Nian Lamei "Girl with a floral garland".
Keywords: Overseas Chinese literature; Thai literature in Chinese; Thai-Chinese literature; Nian Lamei; Girl with a floral garland